Habitat partitioning among three predatory fish in a temperate reservoir. Issue 1 (15th June 2021) - Westrelin, Samuel; Cucherousset, Julien; Roy, Romain; Tissot, Laurence; Santoul, Frédéric; Argillier, Christine
Abstract: The diversity of predatory species plays a key role in ecosystem functioning but our understanding of the mechanisms underlying their coexistence is limited, particularly in freshwater ecosystems. Northern pike Esox lucius, European perch Perca fluviatilis and pikeperch Sander lucioperca are three widespread predatory species in European lakes, where they often coexist. As potential competitors, we hypothesised that partitioning habitat is a determinant of species coexistence. This was tested by quantifying the variability of their habitat use in tracking adult individuals in the Bariousses reservoir (France, 86.6 ha, mean depth 7.1 m). Specifically, we investigated their distribution along the littoral–pelagic and depth axes along the daily cycle and across seasons. From littoral to pelagic waters were first found pike, then perch and finally pikeperch. Pike was the closest to the surface while pikeperch was the deepest. This general pattern was, however, variable across seasons with the three species located in the upper layer in summer during reservoir stratification. Individuals were more evenly distributed along the littoral–pelagic axis and closer to the bottom when water was mixing (autumn, winter). In summer, perch used more intensively in the pelagic zone during the daytime. Other species did not show any diel change of habitats. Our results highlighted that species coexistence is associated with habitat partitioning among these three predators, with perch showing a more variable behaviour regarding habitat characteristics. Now more than ever, in the context of global change which modifies habitats, it is of crucial importance to understand the coexistence mechanisms of species that shape ecosystems.